1998
DOI: 10.1099/0022-1317-79-2-395
|View full text |Cite
|
Sign up to set email alerts
|

Turnip yellow mosaic virus isolates with experimentally produced recombinant virion proteins.

Abstract: The consensus secondary structure of the virion proteins (VPs) of tymoviruses was predicted from their amino acid sequences using a combination of computer methods : profile alignment, hydrophobicity moment and ' PredictProtein '. All methods predicted that they were eight-stranded anti-parallel β-barrels with two α-helical regions. The predicted structure was used to design recombinants of turnip yellow mosaic virus (TYMV) in which selected parts of its VP were replaced with homologous regions of belladonna m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This result suggests that the mutations influenced another process besides encapsidation. Indeed, if only encapsidation initiation was affected, then a delay in the development or a complete absence of systemic symptoms would be expected, while the development of local symptoms would be expected to be similar to that seen with the wild type (3,12). The different stabilities of the various HP1 mutants might explain this result, since the delay in symptom development was apparently linearly related to the calculated stability (Fig.…”
Section: Construction Of Mutantsmentioning
confidence: 89%
“…This result suggests that the mutations influenced another process besides encapsidation. Indeed, if only encapsidation initiation was affected, then a delay in the development or a complete absence of systemic symptoms would be expected, while the development of local symptoms would be expected to be similar to that seen with the wild type (3,12). The different stabilities of the various HP1 mutants might explain this result, since the delay in symptom development was apparently linearly related to the calculated stability (Fig.…”
Section: Construction Of Mutantsmentioning
confidence: 89%
“…13.6) is an RNA plant virus within the family of tymoviridae, which contains at least 20 different known species, among which three have been determined at near-atomic resolution. Selective replacements on TYMV with the homologous regions of another tymovirus, belladonna mottle virus (BeMV), had not affected the infectivity in Chinese cabbages [108]. Six of 10 such recombinants were fully viable and gave symptoms in the plants.…”
Section: Heterologous Peptide Insertionsmentioning
confidence: 96%
“…According to this study, the amino-terminus region was particularly amendable to short peptide substitutions. The first 9 amino acids were successfully replaced with 9 amino acids from E-71 major merozoite surface antigen of Plasmodium falciparum to generate chimeric TYMV particles [108]. However, the study indicated that these residues reacted poorly to the antibodies raised against the E-71 epitope and the antigenic inserts were weakly immunogenic [108], suggesting that these inserts were less accessible to the surface.…”
Section: Heterologous Peptide Insertionsmentioning
confidence: 99%
“…Hayden et al . (18) replaced 10 selected parts of TYMV CP with those of Belladonna mottle tymovirus (BeMV). When inoculated, 6 of the 10 recombinants were viable, and gave rise to symptoms in Chinese cabbage.…”
Section: Introductionmentioning
confidence: 99%
“…As far as C-terminal modifications are concerned, Hayden et al . (18) reported that the mutant where C-terminal 9 amino acid residues were replaced with BeMV did not produce systemic symptoms or local lesions. In contrast, Bransom et al .…”
Section: Introductionmentioning
confidence: 99%